FACTORS ASSOCIATED WITH UNSAFE BEHAVIOR ON WORKERS IN THE PRODUCTION DIVISION OF PALM OIL PROCESSING PT. X - Meisye Herlen Selfia; T Samsul Hilal; Entianopa Entianopa (Jurnal Inovasi Penelitian, 2022)
Unsafe behavior takes many forms from a simple failure to wear or use personal protective equipment to an intentional act, such as moving a guard machine or tampering with a security mechanism into a security system. There are many reasons why people behave unsafely, perhaps they were taught certain unsafe work methods early in the job and see it now as standard work practice, they may lack the skills or knowledge to perform tasks safely, as in certain manual handling, they may failed to secure the load due to timely demands. Factors causing accidents and poor health. The main causes of accidents in the workplace are caused by unsafe behavior and employers need to be aware that reducing accidents can only be achieved by identifying, examining and focusing these behaviors. This research was conducted using a quantitative method with a cross-sectional approach. The population in the study were all workers in the production division of PT.X, totaling 65 people. The sample in this study used total sampling, namely all workers in the production division of PT. X as many as 65 people. Data collection in this study was carried out using questionnaires and interviews. Data were analyzed by univariate and bivariate with chi-square. The results showed that there was a significant relationship between attitudes (p-value = 0.035), knowledge (p-value = 0.041), training (p-value = 0.043) on unsafe behavior in workers in the production division of palm oil processing PT. X in 2021. It is recommended for companies as input and consideration for companies in their work in order to prevent work accidents